The empty seashell witchcraft and doubt on an Indonesian island - Bubandt, Nils (NUS Press, 2015)
"Explores what it is like to live in a world where cannibal witches are undeniably real, yet too ephemeral and contradictory to be an object of belief. In a book based on more than three years of fieldwork between 1991 and 2011, Nils Bubandt argues that cannibal witches for people in the coastal, and predominantly Christian, community of Buli in the Indonesian province of North Maluku are both corporeally real and fundamentally unknowable."--